PENGARUH SUMBER DAYA INSANI DAN FASILITAS TERHADAP KINERJA KARYAWAN DI BANK SUMUT SYARIAH CABANG MEDAN RINGROAD - Putri Khoiriah; Ahmad Adib Nasution; Eli Agustami (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
This study aims to determine the effect of human resources and facilities on employee performance at Bank Sumut Syariah Medan Ringroad Branch. The sample population in this study was 30 employees of Bank Sumut Syariah Medan Ringroad Branch, while the data collection technique used a questionnaire (questionnaire). Data analysis techniques collect normality test, linearity test and multiple linear regression analysis and hypothesis testing, namely partial test (t-test), simultaneous test (F-test), and the coefficient of determination. Based on the results of data analysis using the SPSS 16.0 program, the research hypothesis that uses multiple linear regression testing. This means that if the constant, which means that if the variables X1 and X2 are equal to zero, then Y. X1 regression coefficient value indicates if X1 has increased by 100% it will increase learning outcomes. X2 regression coefficient value indicates if X2 has increased by 100% it will increase human resources. The results of the hypothesis test using the facility t-test obtained the value of tcount ttable, with a probability. The results of the hypothesis test of human resources t-test obtained that the value of tcount ttable with a probability. The results of the simultaneous test (F test) obtained a significant. If we compare the value of Fcount with Ftable, the result. The result of the coefficient of determination (R2) shows that the Rsquare meaning that human resources and facilities are able to explain the performance of employees at Bank Sumut Syariah Medan Ringroad Branch.